2015
DOI: 10.1520/mpc20150001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Composition and Prior Deformation on Phase Transformation Temperatures and Hardness in Direct Quenching Using Physical Simulation

Abstract: For conventional reheated and quenched (RQ) steels, the level of alloying necessary to achieve a given hardenability and hardness can be estimated from calculated Jominy curves or ideal critical diameters (DI) given in ASTM A255-10(2014). However, for thermomechanically rolled direct quenched (DQ) steels, little data are available. In this study, the accuracy of the ASTM approach was estimated by designing an experiment to study the main effects of seven alloying elements (C, Mn, Cr, Ni, Mo, Nb, and V) at two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…A comparison of the predictions made using the newly developed CCT equations based on the grain boundary composition and those developed previously based on nominal bulk composition has also been made, particularly with respect to the CCT measurements of high-carbon steels given in the literature. The results of the current study can also be complemented by the effect of thermomechanical processing [15][16][17][18] taking place in many steel processing operations. [19] On the other hand, the current method using IDS to include the effect of deformation on phase transformations and precipitation is still quite approximate and needs to be developed further.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the predictions made using the newly developed CCT equations based on the grain boundary composition and those developed previously based on nominal bulk composition has also been made, particularly with respect to the CCT measurements of high-carbon steels given in the literature. The results of the current study can also be complemented by the effect of thermomechanical processing [15][16][17][18] taking place in many steel processing operations. [19] On the other hand, the current method using IDS to include the effect of deformation on phase transformations and precipitation is still quite approximate and needs to be developed further.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a wide range of dislocation substructures in the austenite before the quench can be produced. While the focus of this study is on lath martensite microstructures, TMP can influence the hardenability during direct quenching and other microstructures with variations in strength and toughness can be produced depending on the cooling rate [5].…”
Section: Introductionmentioning
confidence: 99%
“…Where direct quenching is concerned, the data are scarce and often proprietary. The use of the ASTM standard as such has been found to be inappropriate in the case of direct quenching [5]. Fresh attempts were made to develop new hardenability models through non-linear regression analysis by dynamically varying both the boron factor and multiplying factors of most elements in the alloy factor [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the ASTM standard A255-10, distance hardness dividing factors for both non-boron and boron steels have been provided for a large number of ideal critical diameters in separate tables[4]. A preliminary analysis suggested that if the structure of the approach to calculating DI B is considered correct, then the terms a Mo and a Cr are too large[5]. Alternatively, the boron factor is perhaps not described well as a function of AF, particularly beyond AF > 26.Because of inherent difficulties with the complex form of DI B (Eqs.…”
mentioning
confidence: 99%
See 1 more Smart Citation